Wissensabsorption - die Stadt als Magnet. - Einem, Eberhard von (TH Zürich, NSL, 2009)
Der Beitrag plädiert - aus einer erweiterten wirtschaftsgeographisch-regionalwissenschaftlichen Perspektive - für einen Prioritätenwechsel. Statt den Blick immer nur auf den numinosen Akt der Generierung von neuem, kreativem, innovatorischem Wissen zu richten, schlägt er vor, Prozesse der Wissensabsorption neugieriger zu beobachten. Dynamiken der schnellen Wissensabsorption sowie die Fähigkeit einiger Stadtregionen, neues Wissen und kreative Köpfe besonders erfolgreich an sich zu ziehen (durch institutionelle Talentmagneten etwa), hält der Autor für eine grob unterschätzte Zentralkomponente in der Koevolution von Raum, Wissen und Milieus. Möglicherweise sei es sogar ein entscheidendes fehlendes Glied, um aus Stadtregionen, die sich zukunftsfähiger machen wollen, lernende Stadtregionen zu machen.

The paper explores the dynamics of the knowledge absorption process and its locational conditions in cities and regions. Because both firms and governments cannot rely on generating new knowledge themselves through research and development only, the absorption of new ideas, concepts an technologies created elsewhere around the world seems to be important for staying on top in the race for global competitiveness. Imported knowledge needs to be combined with locally available knowledge in order to update one's own products and services. However, linking into the international diffusion of knowledge firms and government agencies depends on having prior related knowledge, both codified and tacit. To take a model analogy from medical infection research: the recipient's opportunity to be infected by new knowledge that is circulating depends on both his predisposition and the frequency of his contacts. Cities and regions act as magnets, attracting talented people (migration) and developing diverse labor pools, thus allowing for agglomeration effects and reduced time-lag, in picking, up new knowledge.
Knowledge absorption - The city as magnet.
Keywords: Raumordnung; Region; Stadtregion; Regionalwissenschaft; Raumplanung; Planungstheorie; Planungspraxis; Raumforschung; Raumwissenschaft; Raumentwicklung; Bildung; Wissenschaft; Planungswissenschaft; Wissensregion; Wirtschaftsregion; Kreativität; Wissensanwendung; Wissenschaftsstadt; Wissen; Milieu; Kreatives Milieu; Wissenstransfer; Netzwerk; Governance; Nachhaltigkeit; Lernen; Lernende Region; Wissensgesellschaft; Wissenssoziologie; Raumkategorie; Städtewettbewerb